The Song of Hiawatha - Longfellow, Henry Wadsworth 1807-1882 (Dover Publications, 2006)
The infectious rhythm of The Song of Hiawatha has drawn millions to the shores of Gitchee Gumee. Once there, they've stayed to hear about the young brave with the magic moccasins, who talks with animals and uses his supernatural gifts to bring peace and enlightenment to his people. This 1855 masterpiece combines romance and idealism in an idyllic natural setting.